Compulsive Bowel Emptying and Rectal Prolapse in Eating Disorders. Presentation of Two Cases - Fragiskos Gonidakis; Georgios Georgantopoulos; Olga Theodoropoulou; Eleftheria Varsou (Archives of Depression and Anxiety - Peertechz Publications, 2015)
Eating Disorders are a heterogeneous group of complex psychiatric disorders that affect physical and psychological functioning, thus compromising life itself. They are often characterized by extreme preoccupation with food, caloric intake and expenditure as well as bodily weight and shape. Additionally,  individuals present several forms of recurrent compulsive  behavior,  such  as  frequent weighting, body checking, and eating rituals. In many cases food consumption is considered a" failure" and its presence in the body "harmful and even "toxic" leading the individual to adopt a wide variety of purging behaviors in order to achieve a state of mental and physical "cleanliness" Two cases of compulsive bowel emptying, one suffering from Anorexia Nervosa and one suffering from  Bulimia Nervosa, are presented. The compulsive bowel emptying  behavior compromised of repeated and/or prolonged voluntary tension of the abdominal and pelvic muscles as well as insertion of  the  figure  in  the  rectum  to  "check" if  the  bowel  has  been  completely  empty  of  its  content. The purpose of this behavior was to alleviate  intense anxiety caused by obsessive thoughts that  the individual  would  get  "fat"  and/or  "dirty/intoxicated"  if the bowel  was  not  completely  vacated of  the stools. In both cases the compulsive  behavior  facilitated  the  manifestation  of  rectum  prolapse  that reinforced the vicious circle of the obsessive-compulsive symptomatology.